Decoupage Training for Community Kampung Sawah, Bekasi Town - Yanti Murni; Hirdinis M.; M. Ali Iqbal (MITRA: Jurnal Pemberdayaan Masyarakat, 2018)
The community service team of Unversitas Mercu Buana Jakarta held entrepreneurship training for the community, especially for the young generation and housewives who do not have job, and to grow entrepreneurship spirit as well as explore their potential. The entrepreneurship training was expected to bring new business and give a positive effect on the development of independent spirits of the younger generation and housewives in their efforts of earning additional income. The Decoupage Training for the Kampung Sawah Kota Bekasi community aimed to i) foster enthusiasm, motivation and entrepreneurial creativity for the community and ii) to provide sufficient knowledge and skills so that the participants could obtain the entrepreneurship spirits. The participants consisted of 22 teenage girls who dropped out of school and unemployed housewives. We believe that the training brought good results and we hope that in the future the creativity of the community can be developed and enhanced into a productive business to support family finances.